2013
DOI: 10.1007/s12032-013-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the willingness of US women to vaccinate their daughters against the human papillomavirus to prevent cervical cancer

Abstract: The human papillomavirus (HPV) vaccine helps to prevent cervical cancer. However, research indicates that public acceptance of the vaccine is suboptimal. Our aims were to evaluate the willingness of US women to use the HPV vaccine in their daughters, examine their current understanding of HPV, and determine the impact of HPV knowledge and other socio-demographic factors on their willingness to get their daughters vaccinated. Women aged ≥ 18 years were identified from the US Health Information National Trends S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
2
11
1
1
Order By: Relevance
“…2931 For instance, in Connecticut, 32 heterogeneity in the occurrence of cervical cancer precursors is reported. Culturally competent locally targeted outreach needs to be part of cervical cancer control programs.…”
Section: Discussionmentioning
confidence: 99%
“…2931 For instance, in Connecticut, 32 heterogeneity in the occurrence of cervical cancer precursors is reported. Culturally competent locally targeted outreach needs to be part of cervical cancer control programs.…”
Section: Discussionmentioning
confidence: 99%
“…13 While not universally accepted, one of the suggested interventions to improve HPV vaccine uptake is increasing HPV and HPV vaccine knowledge. [14][15][16] Previous studies have demonstrated that HPV knowledge and awareness is associated with interest in receiving the HPV vaccine, 17 acceptance of the HPV vaccine, 18 intent to receive the HPV vaccine, 19 and actual uptake of the HPV vaccine. 20 Similarly, HPV awareness among parents of adolescent children is associated with a greater interest in having one's child vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…HPV vaccine series completion, which included three doses in 2015, was recently estimated at 35% in the U.S. Factors contributing to low population-level HPV vaccine coverage are not well understood. Parents are generally aware of the HPV vaccine [ 2 ], but specific knowledge about HPV vaccination (e.g., schedule, benefits) is weakly correlated with actual coverage [ 3 ]. While multiple causes likely exist, low coverage is hypothesized to be a function of hesitancies, ambivalence, or resistance by many parents who are deciding about their child’s healthcare.…”
Section: Introductionmentioning
confidence: 99%